The Formation of Political Preferences Among Generation Z in the Prabowo-Gibran Campaign on Instagram - Prayogo, Agung; Aminuddin, Aminuddin (Vox Populi, 2025)
This research highlights the political preferences of Generation Z within the context of the Prabowo-Gibran campaign on Instagram, a platform that has become a vital arena for shaping political imagery in the digital age. Through visual content analysis with a netnographic approach, this study explores how visual communication strategies and personal narratives are designed to respond to the dynamics of Generation Z’s political preferences—a generation known for being critical, visually oriented, and hungry for authentic representation. The findings reveal that Prabowo presents himself as a firm nationalist figure, symbolizing stability and traditional strength, while Gibran positions himself as an inclusive young leader, rooted in local innovation and the aspirations of a new generation. The use of aesthetic elements such as modern visual design, strategic hashtags, and the integration of AI reflects a clever adaptation to the digital language of Generation Z, which seeks not only information but also emotional and aesthetic experiences. This study uncovers that the political preferences of Generation Z in the Prabowo-Gibran campaign on Instagram are influenced not only by the substance of political messages but also by the campaign's ability to engage collective imagination through fresh, interactive, and relevant visual mediums. In modern democracy, Instagram is no longer merely a campaign tool but a primary battleground for symbolic struggles that shape the political preferences of the youth.